Escolas bilíngues de fronteira: inclusão de discentes venezuelanos nas escolas municipais da área urbana de Pacaraima - Paz, Sandra Elaine Trindade da (Universidade Federal de Roraima, 2022)
The research "Frontier Bilingual Schools: inclusion of Venezuelan students in schools of urban area Pacaraima", aimed to analyze the social inclusion of students who daily cross the border line, enrolled in schools participating in the Bilingual Schools Program Frontier in Pacaraima, a small town in the state of Roraima. The research, according to identity, cultural diversity and inclusion theories in Brazilian educational system, identifyes the public policies implemented in the education system that consider the social inclusion of these students, contextualizing the role of the school in the face of cultural diversity, analyzing the curricular practices developed in the context of the classroom. As methodological procedures, there was a documental search in public agencies such as: Pacaraima City Hall; Municipal Department of Education Pacaraima; in schools enrolled in the Bilingual Schools Program Frontier urban area of Pacaraima, with their secretariats, with access enrollment of students; the Brazilian Institute of Geography and Statistics; in addition to the School Census data collection, through the National Institute of Educational Studies Anísio Teixeira. The field research was through participant observation in municipal schools Alcides da Conceição Lima and Casimiro de Abreu, which are part of the Bilingual Schools Program Frontier. We used inductive method, analyzing and describing the actions as the inclusion of students Venezuelans in the school context and in the classroom during the learning process. It was found that since 2009 the Bilingual School Programme Border, in this city is not running, caused by political and economic problems, however more than 30% of students of the two schools cross the border line to study in Brazil. The nationalist identity of the Venezuelan student is present in the activities developed in the classroom, but is not emphasized in the school environment. The inclusive process occurs at all levels of the education sector from the municipal manager who pays the transportation to the receptivity dispensed by the teacher, who hosts with respect, experiencing a harmonious coexistence between students students and teachers/students.